PRELIM - UTHM, penerbit (Journal of Techno-Social, 2015)
1. PATRONAGE2. SCIENTIFIC ADVISORY BOARD3. EDITORIAL BOARD4. ASSOCIATE EDITOR5. EDITORIAL MANAGEMENT COMMITTEE6. MESSAGE FROM EDITOR IN CHIEF7. CONTENTS